Process analysis of mercury adsorption onto chemically modified rice straw in a fixed-bed adsorber. Issue 2 (June 2016) - Song, Shiow-Tien; Hau, Ying-Fong; Saman, Norasikin; Johari, Khairiraihanna; Cheu, Siew-Chin; Kong, Helen; Mat, Hanapi
Highlights: Low flow rate, high feed concentration and bed height increase the Hg adsorption. The continuous adsorption data followed Langmuir isotherm model. The adsorption data fits Thomas and Yoon–Nelson models. The adsorption–desorption process retains more than 90% removal rate after four cycles. Yoon–Nelson model was used in the prediction of breakthrough curve using EBCT value. Abstract: The potential application of chemically modified rice straw (RSGM) was investigated in a fixed-bed adsorber as an extension of our previous batch adsorption studies. The effect of flow rates (2 mL/min, 4 mL/min and 8 mL/min), Hg(II) concentrations (50 mg/L, 100 mg/L, and 200 mg/L), and bed heights (1.5–4.5 cm) on the breakthrough characteristics of the fixed-bed adsorber was investigated. The adsorption isotherm data were best fitted to the Langmuir isotherm model, while the breakthrough data were found to be in good agreement with the Thomas and Yoon–Nelson models. The adsorbent bed regeneration results indicate a good adsorption–desorption reversibility with retaining adsorption performance of more than 90% after four cycles. The process design of the fixed-bed adsorber was demonstrated using the height of an equivalent transfer unit (HETU) method. The prediction of breakthrough curve was successfully carried out by scaling-up the Yoon–Nelson constants obtained from empty bed contact time (EBCT) plots.